2017
DOI: 10.1007/s10753-017-0604-7
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction of LPS and RSV Infection in Augmenting the AHR and Airway Inflammation in Mice

et al.

Abstract: Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory tract infection (LRTI) in children under 5 years of age, especially infants with severe bronchiolitis. Our preliminary clinical experiments showed that bacterial colonization was commonly observed in children with virus-induced wheezing, particularly in those with recurrent wheezing, suggesting that bacterial colonization with an accompanying viral infection may contribute to disease severity. In most cases, RSV-infected infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…These findings support how RSV may cause neurological irregularities in patients (Eisenhut, 2006;Li et al, 2006;Morichi et al, 2017). Several studies have described an association between lower respiratory tract RSV infection in infancy and the subsequent development of persistent wheezing in children (Zhou N. et al, 2017;Zhong et al, 2018). In mice, RSV induces long-term airway disease characterized by chronic airway inflammation and airway hyperreactivity (Long et al, 2016;Zhou N. et al, 2017), and RSV antigens have been detected in the lungs >100 days (Schwarze et al, 2004).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…These findings support how RSV may cause neurological irregularities in patients (Eisenhut, 2006;Li et al, 2006;Morichi et al, 2017). Several studies have described an association between lower respiratory tract RSV infection in infancy and the subsequent development of persistent wheezing in children (Zhou N. et al, 2017;Zhong et al, 2018). In mice, RSV induces long-term airway disease characterized by chronic airway inflammation and airway hyperreactivity (Long et al, 2016;Zhou N. et al, 2017), and RSV antigens have been detected in the lungs >100 days (Schwarze et al, 2004).…”
Section: Introductionsupporting
confidence: 59%
“…Several studies have described an association between lower respiratory tract RSV infection in infancy and the subsequent development of persistent wheezing in children (Zhou N. et al, 2017;Zhong et al, 2018). In mice, RSV induces long-term airway disease characterized by chronic airway inflammation and airway hyperreactivity (Long et al, 2016;Zhou N. et al, 2017), and RSV antigens have been detected in the lungs >100 days (Schwarze et al, 2004). However, RSV persistence does not appear in the bronchial epithelium (the primary site of viral replication) but in deeper lung structures (Long et al, 2016;Zhou N. et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, the acute (7 d) and chronic (28 d) infection model of RSV infection was established by intranasal injection of RSV into guinea pigs [ 8 , 23 ]. We found that during the acute infection period (7 d), epithelial cells shed in the lung tissue, and a large number of inflammatory cells infiltrated in the microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…Other mice were administered intranasally with either andrographolide sulfonate at 20 µl (0.5 mg/mice/d) or normal saline on day 0 (2 h post-RSV infection) and days 1 to 4, consecutively. According to the previous data of the research group, it was found that the lung in ammation was most obvious on the 5th day after RSV infection in mice (Zhou et al, 2017). So all mice were sacri ced on day 5 post RSV infection.…”
Section: Rsv Infection and Andrographolide Sulfonate Treatmentmentioning
confidence: 93%